The THE EFFECT OF THE AUDIO LINGUAL METHOD ON STUDENTS’ SPEAKING ACHIEVEMENT - Usman Sidabutar (Fakultas Keguruan dan Ilmu Pendidikan, Universitas HKBP Nom- mensen, 2021)
The objective of this research is to find the effect of the Audio- Lingual Method on speaking achievement of the second grade of students on English Department of the HKBP Nommensen University Medan in academic year 2018/ 2019 which is focused on dialog speaking encompassing the pronunciation, vocabulary, grammar, fluency, and comprehension. This design of the research was the experimental quantitative design which applied two variables, such as a dependent variable as a speaking ability and an independent variable as an Audio- Lingual Method. Having analyzed the data, the writer found that the Audio- Lingual Method affects students’ speaking ability. There was a different mean score obtained from the both control group 65, 28 and the experimental group is 8,031. The result of the calculation is: Tabs > table (P= 0.05); (df= 48) And 8,031 > 2,010 (P = 0.05); (df = 48). The alternative hypothesis of the method is accepted. The students’ speaking ability by using the Audio- Lingual Method shows better results compared to those who did not teach by using the Audio- Lingual Method. It is suggested for English teacher to use the Audio- Lingual Method as the way to improve the students’ English speaking ability.